Prokinetic effect of erythromycin in the management of gastroparesis in critically ill patients—our experience and literature review - Szczupak, Mateusz; Jankowska, Magdalena; Jankowski, Bartłomiej; Wierzchowska, Jolanta; Kobak, Jacek; Szczupak, Paweł; Kosydar-Bochenek, Justyna; Krupa-Nurcek, Sabina (Frontiers in Medicine, 2024)
Gastroparesis is a disorder characterized by impaired gastric emptying and the accumulation of food in the intestines without any clear mechanical cause. Gastroparesis in critical care patients is a prevalent issue in the intensive care unit. The disruption of normal gastrointestinal motility in critically ill patients is linked to a significant risk of intolerance to enteral feeding, colonization of the gastrointestinal tract with pathogenic bacterial strains, increased permeability of the intestinal wall, translocation of the intestinal microbiota, leading to progressive malnutrition, and potential development of bacterial infection. Material and methods: The literature was reviewed to assess the benefits and risks associated with the use of this medication. Aim: The aim of the study was to treat the symptoms of gastroparesis and stimulate gastrointestinal motility. Consequently, the aim was to reduce the amount of backed-up food content in the stomach, accelerate gastrointestinal motility, and return to intestinal feeding. Results:Gastroparesis is a frequent issue among patients in the intensive care unit. Critical illness can lead to gastrointestinal motility disorders, causing slowed gastric emptying. This increases the risk of problems such as intolerance to enteral feeding, regurgitation, and aspiration of gastrointestinal contents into the respiratory tract, as well as colonization of the gastrointestinal tract by pathogens. Over time, impaired intestinal absorption can result in malnutrition, necessitating the initiation of parenteral nutrition. Conclusion: After analysis of the literature and published scientific reports, as well as considering their own research, it is evident that erythromycin, as a prokinetic drug, effectively enhances gastrointestinal motility. This contributes to stimulating gastric emptying in critically ill patients with gastroparesis who are hospitalized in an intensive care unit. The use of erythromycin in combination with metoclopramide and/or itopride hydrochloride allows for a synergistic effect, leading to the quickest possible return to enteral feeding.